Reporting simplified colonic transit studies using radionuclides: clinician friendly reports. Issue 2 (February 1995) - Notghi, A; Mills, A; Hutchinson, R; Kumar, D; Harding, L K
Abstract : This study describes a graphic presentation of the results of a simplified segmental colonic transit model. This study requires three sets of images on three consecutive days after intake of indium-111 resin capsule at each time point. The per cent of ingested activity is calculated in each region of the colon and in the faeces. The program uses standard PC compatible graphic package, CorelDRAW (Corel Corporation). The report for the patients' notes consists of three schematic diagrams of colon with regions identified and a pot representing the faecal activity. The per cent of administered activity in each region and pot is both printed and represented by shades of grey (white representing 0% and black 100% activity), for each region and the pot. The distribution of activity is clearly seen at each time point and the report is presented on single A4 size sheet of paper. Using a simplified colonic study protocol it is possible to produce clinician friendly reports on a single sheet of paper.